Teilhard de Chardin's vision of science, religion and planetary humanity: a challenge to the contemporary world - King, Ursula (Journal for the study of religion, 2018)
Teilhard de Chardin (1881-1955) was a great thinker, scientist, and mystic - he was above all an extraordinary human being whose inspiring vision still remains far too little known. He visited South Africa twice, in 1951 and 1953, to undertake palaeontological research and collaborate with South African colleagues. Throughout his life, but especially towards its end, he was much interested in the future of planetary humanity and he always stressed the importance of seeing, of having a vision that pulls us forward and upward. For him, life is vision. I examine how this vision - embracing science, religion and the future of humankind - presents a challenge to the contemporary world and an inspiration to create a better future for all.I first look at our world in crisis, dominated by science, but politically fragmented, suffering from much injustice, poverty and violence. Where are we going? Teilhard's evolutionary, convergent and universalist thinking can be a guiding light for the contemporary world to move forward.At the present state of crisis, planetary humanity is faced, more than ever before, with the responsibility for its further self-evolution. Has the human species the evolutionary capacity for developing its life to a higher stage, for truly transformative action to create greater collaboration and unification, more universal peace and justice? This is a decisively critical question, for to evolve further is no longer just an option, but an imperative.What are the spiritual energy resources needed for the further development of the human community, especially the necessary zest for life, the all-transforming power of love and compassion available in order to develop an environmentally and ecologically sound way of life to ensure the wellbeing of all people and the planet? In order to be able to evolve further, we need a new spiritual awakening, and a deeply mystical, action-oriented spirituality in the contemporary world. I hope to show that Teilhard's integral vision, rooted both in modern science and a fervent faith, can be an empower-ing vision for us all.Keywords: science, religion, planetary humanity, vision, the future of humankind, self-evolution, evolutionary capacity, universal peace and justice, spiritual energy, zest for life